Increasing Oil and Gas Well Productivity in Offshore Conditions - Novruzova, S.H.; Aliyev, I.N. (Herald of Azerbaijan Engineering Academy, 2024)
In a situation where the demand for oil and gas is increasing day by day, there are reductions in production due to several reasons. As we know, the productivity of the well depends on several factors. These factors are examined and detailed information is provided in this article. Among the main issues, processes such as hydraulic fracturing and acid treatment have been investigated in order to improve the conductivity of the well bottom zone. In addition, the relationship between reducing the back resistance at the wellhead and choosing the optimal mode for increasing the flow rate of the well was also considered. Attention has been paid to the importance and possibility of taking preventive measures against the problems identified as a result of the research conducted in this direction. Among the preventive measures taken against the sand problem, which is one of these problems, gravel packing, metal strainer, and chemical hardening methods were investigated. In addition, attention has been paid to the issue of increasing the flow from the formation to the well by removing the fluid collected at the bottom of the well.